Cacna1c haploinsufficiency leads to pro-social 50-kHz ultrasonic communication deficits in rats - Kisko, Theresa Marie; Witt, Stephanie; Rietschel, Marcella (Disease models & mechanisms, 2018)
The cross-disorder risk gene CACNA1C is strongly implicated in multiple neuropsychiatric disorders, including autism spectrum disorder (ASD), bipolar disorder (BPD) and schizophrenia (SCZ), with deficits in social functioning being common for all major neuropsychiatric disorders. In the present study, we explored the role of Cacna1c in regulating disorder-relevant behavioral phenotypes, focusing on socio-affective communication after weaning during the critical developmental period of adolescence in rats.
Gesehen am 23.10.2019